2013
DOI: 10.1152/ajpcell.00034.2013
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac sodium current Nav1.5 is functionally expressed in rabbit bronchial smooth muscle cells

Abstract: Bradley E, Webb TI, Hollywood MA, Sergeant GP, McHale NG, Thornbury KD. The cardiac sodium current Nav1.5 is functionally expressed in rabbit bronchial smooth muscle cells. Am J Physiol Cell Physiol 305: C427-C435, 2013. First published June 19, 2013 doi:10.1152/ajpcell.00034.2013.-A collagenase-proteinase mixture was used to isolate airway smooth muscle cells (ASMC) from rabbit bronchi, and membrane currents were recorded using the whole cell patch-clamp technique. Stepping from Ϫ100 mV to a test potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Veratridine at 50-100 µM inhibits the peak current of Nav1.4, Nav1.5, Nav1.7, Nav1.2, and Nav1.6 in HEK293 cells to different extents and enhances the sustained inward current and tail current in all of these channels [11,41,42]. Our data confirmed these effects of veratridine on Nav1.7, suggesting that veratridine has a general effect on these three parameters in different subtypes of VGSCs.…”
Section: Discussionsupporting
confidence: 77%
“…Veratridine at 50-100 µM inhibits the peak current of Nav1.4, Nav1.5, Nav1.7, Nav1.2, and Nav1.6 in HEK293 cells to different extents and enhances the sustained inward current and tail current in all of these channels [11,41,42]. Our data confirmed these effects of veratridine on Nav1.7, suggesting that veratridine has a general effect on these three parameters in different subtypes of VGSCs.…”
Section: Discussionsupporting
confidence: 77%
“…The APD90 was increased over twofold by veratridine 1 μM, with a good reversibility upon wash-out ( Table 2), and an even higher prolongation with 5 μM ( Figure 4), although in this case we were unable to accurately compute APD90 values for externally paced APs, due to their overlap with the next stimulus. This effect is consistent with the findings of previous studies, showing APD prolongation in bronchial smooth muscle cells upon veratridine application 32 , and the enhancement of AP burst generation by veratridine in rat trigeminal sensory neurons 33 . Furthermore, we have demonstrated that hERG inhibition does not play any role in the observed APD prolongation by veratridine at 1 or 5 μM, since significant hERG inhibition occurred with higher veratridine concentrations ( Figure 5).…”
Section: Discussionsupporting
confidence: 93%
“…The recent evidence presented by Bradley et al (65) regarding the expression of a voltage-dependent Na + current in freshly dispersed rabbit bronchial myocytes seemingly mediated by the Nav1.5 α subunit, cannot be overlooked. When this current in bronchial myocytes was pharmacologically altered (blocked with veratridine), their action potential was prolonged.…”
Section: Na+ Voltage Dependent Currents In Airway Smooth Musclementioning
confidence: 95%